2006
DOI: 10.1007/s00586-006-0258-x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of standalone balloon kyphoplasty with calcium phosphate cement augmentation in traumatic fractures

Abstract: Prospective consecutive series cases study to investigate the clinical and radiological results of standalone balloon kyphoplasty and cement augmentation with calcium phosphate in traumatic fractures. Independent observer evaluation of radiological and computer tomography results, visual analogue scale (VAS), Roland-Morris score and complications with acute traumatic compression fractures type A, treated with a standalone balloon kyphoplasty and cement augmentation with calcium phosphate (Calcibon TM ); follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(76 citation statements)
references
References 29 publications
0
73
0
3
Order By: Relevance
“…The development of new minimal invasive strategies can be therefore an interesting alternative for the treatment of burst fractures and the results of a recent prospective study [6] with standalone balloon kyphoplasty showed satisfactory outcomes, especially for A3.1 fractures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The development of new minimal invasive strategies can be therefore an interesting alternative for the treatment of burst fractures and the results of a recent prospective study [6] with standalone balloon kyphoplasty showed satisfactory outcomes, especially for A3.1 fractures.…”
Section: Discussionmentioning
confidence: 99%
“…1) was measured on the sagittal reconstructions, using two indices: first by comparing the height of the anterior face of the fractured vertebral body with that of the adjacent body both pre-and post-operatively, as described by Acosta [10]; and secondly, using the Beck index, as described by Maestretti [6], to compare the height of the anterior face of the fractured vertebral body with that of the posterior face of the same body. The presence of any local segmental vertebral kyphosis was checked both before and after surgery.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maestretti et al used percutaneous augmentation with CPC alone without posterior stabilization in the treatment of thoracolumbar compression and burst fractures. 25 Inclusion criteria included fracture with at least 15° of kyphosis in patients with a single traumatic injury or 10° in those with more than one traumatic injury or with multilevel fractures without any neurological deficit. The authors reported good outcomes with a standalone procedure both clinically and radiographically.…”
Section: Percutaneous Anterior Column Augmentationmentioning
confidence: 99%
“…The paper by Maestretti et al [30] in which a calcium phosphate material is used, with the hope that it will in time be replaced with bone, certainly demonstrates a very effective clinical success, and it is certainly an attractive technique in the multiply injured patient. However, clearly at 3 years, it is not converted to bone, and one must be concerned at the presence of a foreign body, with somewhat unsatisfactory mechanical properties compared with bone, yet occupying a significant part of the vertebral body in some one who may be young.…”
Section: Thoracolumbar Fracturesmentioning
confidence: 99%